THE STUDENTS' BARRIERS IN ENGLISH LEARNING AT IAIN OF MANADO - Nagauleng, Andi Mukarramah (Elite : English and Literature Journal, 2016)
The identification of barriers in the English teaching and learning is essential in providing solutions for students to learn and achieve the expected learning objectives. This article attempts to explore the barriers faced by students of IAIN Manado in learning English as well as offering solutions for lecturers, researchers, and students themselves to overcoming these obstacles. Humans are social beings who cannot live alone without others in interacting and communicating, with their first language English as a second language. By using the English language in good and right uses will make easier for someone to communicate in the classroom with a friend or lecturer who came from another tribe, and spoke in the forum with the impression of a politer. Speak properly not only emphasizes the truth in terms of grammar, but also pay attention to the communicative aspect. The language communicative is not necessarily always the standard language. Instead, use the standard language does not necessarily mean that the use language in good and true uses. Preferably, use of a variety of language that is compatible with the target and in addition follows the rules of correct language.